Non-Figural Motifs on the Roman Funerary Stelae from Upper Macedonia (Problems of Date and Interpretation) - Proeva, Nade (Actual Problems of Theory and History of Art, 2017)
Classical archaeology is deeply rooted in collecting works of art, and this is the reason why theearlier scholarly works focused on artefacts of high artistic value, while artefacts with less significant artistic qualities were totally neglected. An obvious example is a group of funeral stelae with non-figural iconography also known as Tikvesh type stelae spread in the valley alongside the middle course of the Axius (Vardar) River,Upper Macedonia. They display very specific motifs in their relief field as well as in the pediment, e.g. humanfigures shaped in evergreen tree forms, grapevines and ivy leaves, and rosettes, or agricultural tools (hook forpicking grapes, pickaxe etc.). They are dated from the 1st to the 4th century AD, the largest number belonging to the 2nd and 3rd centuries AD. Neglecting the epitaphs and treating the motifs separately and out of context, scholars have reached widely differing interpretations: either that the iconography reveals Celtic beliefs, or that it is Oriental (based on thecults of Men, Attis and Cybele) or that it is Christian and Gnostic, i.e. of Manichean origin. It is worth mentioning that no evidence for such interpretations has ever been found either in written sources, or even in archaeological materials. Dated monuments clearly show that their schematic “naïve” styleis determined by the type of local stones (e.g., gneiss, volcanic tuff, andesite), which is unsuitable for polishing,and cannot be an element for chronology. Also these stelae were carved by the locals, who were pretty unskilled craftsmen.Treating the iconographic composition as a whole, taking the epitaphs into consideration as an integral partof the stelae along with the socio-economic, religious and cultural milieu in which they were created, I have concluded that this unusual iconography was used to express heroization (the epithet héros often occurred inepitaphs) of not only the deceased, but also their ancestors, expressed in an original way, typical of the local population.
Keywords: Roman Macedonia; funerary stelae; iconography; non-figural motifs; heroisation of the deceased; oriental deities; Celtic survivals; Manicheans dogma